Coefficient estimates for two subclasses of analytic and bi-univalent functions - Lashin, A. Y. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce two new subclasses of the class $σ$ of analytic and bi-univalent functions in the open unit disk $U$. Furthermore,we obtain the estimates for the first two Taylor – Maclaurin coefficients $|a_2|$ and $|a_3|$ for the functions from these newsubclasses.